Healthcare professionals´ perception towards environmentally friendly dry powder inhalers in the United Kingdom, Sweden and Germany - Lehto, Ilmari (My University, 2022)
Pharmaceutical industry and the whole health care sector are facing pressures from various stakeholders to be as sustainable and environmentally friendly as possible. These stakeholders include patients, doctors and healthcare professionals, patient associations, governments and regulators, authorities and manufacturers. Pharmaceutical manufacturers are making great efforts to meet regulations around sustainability as well as new innovations. Dry powder inhalers, pressured metered dose inhalers and nebulizers are examples of different types of inhalers that are used to treat asthma, COPD and other respiratory diseases. Inhalers can differ from each other’s with different active pharmaceutical ingredients and how the inhaler device works. This thesis focuses on the environmental friendliness between dry powder inhalers and metered dose inhalers and whether it has an impact on healthcare professionals prescribing habits. The use of dry powder inhaler is more environmentally friendly than the use of metered dose inhaler in terms of carbon dioxide emissions emitted per auction. The difference between the two arises from the way the pharmaceutical ingredients inside the inhaler are transmitted to the patients´ lungs. In dry powder inhalers, the patient itself generates the inspiration and in the metered dose inhalers propellant gases are used to get the pharmaceutical ingredients in to the patients’ lungs. This generates the difference in the environmental friendliness of the two inhaler types. This research method used in this thesis is qualitative and is exploratory by its nature. The primary data was collected through semi-structured interviews and a total of ten different healthcare professionals were interviewed from Sweden, Germany and the United Kingdom. The results from this thesis indicate that healthcare professionals in Sweden, Germany and the United Kingdom do value sustainability and the environmental friendliness of dry powder inhalers have an impact on their prescribing habits. However, the most important factor when prescribing inhalers is patient safety and patients´ ability to use the inhaler correctly in order to guarantee a successful treatment. If the patient is able to use a dry powder inhaler, the prescribing healthcare professional will more likely choose the dry powder inhaler over metered dose inhaler because the dry powder inhaler is more environmentally friendly to use. This can cause a pharmaceutical company that manufactures dry powder inhalers to get more sales and competitive advantage over companies that manufacture only metered dose inhalers. The findings also indicate that it is good that a pharmaceutical company that manufactures dry powder inhalers keeps bringing this information for healthcare professionals around the world. However, the biggest influence towards the change from metered dose inhalers to dry powder inhalers comes from the local authorities that might put up some guidelines and policies around this topic.

Lääketeollisuus sekä koko terveydenhuoltoala kohtaavat paineita useilta eri tahoilta tehdäkseen toiminnastaan mahdollisimman vastuullista ja ympäristöystävällistä. Nämä eri tahot kattavat niin potilaat, lääkärit ja muut terveydenhuollon ammattilaiset, potilasjärjestöt, hallituksen ja muita sääntelijöitä, viranomaiset sekä tuotantoteollisuuden. Lääkevalmistajat panostavat merkittävästi kohdatakseen asetetut säädökset vastuullisuudesta sekä saavuttaakseen uusia innovaatioita. Kuivajauheinhalaattorit, ponnekaasuaerosolit ja nebulisaattorit ovat esimerkkejä eri tyyppisistä inhalaattoreista, joita käytetään astman, keuhkoahtaumataudin ja muiden keuhkosairauksien hoitoon. Inhalaattorit eroavat toisistaan farmaseuttisten ainesosiensa suhteen, mutta myös käyttötavaltaan. Tämä pro gradu -tutkielma keskittyy ympäristöystävälliseen näkökulmaan vertaillessa eroja kuivajauheinhalaattorien ja ponnekaasuaerosolien välillä, sekä onko ympäristöystävällisyydellä merkitystä terveydenhuollon ammattilaisten hoitokäytäntöihin esimerkiksi lääkkeiden määräämisessä. Kuivajauheinhalaattorien käyttö on ympäristöystävällisempää verrattaessa ponnekaasuaerosoliin tarkastellessa hiilidioksidipäästöjä käyttökertaa kohden. Näiden ero selittyy mekanismilla, jolla lääkeaine siirtyy inhalaattorista potilaan keuhkoihin. Kuivajauheinhalaattoreissa potilas itse aiheuttaa hengityksellään sisään virtauksen, jolla vaikuttava lääkeaine päätyy potilaan keuhkoihin. Sen sijaan ponnekaasuaerosoleissa lääkeaineen kulkeutuminen keuhkoihin saadaan aikaan ponnekaasuja apuna käyttäen. Poikkeavuudet mekanismissa aiheuttaa myös eroavuudet ympäristöystävällisyydessä. Tässä pro gradu -tutkielmassa tutkimusmenetelmät ovat kvalitatiivisia ja eksploratiivisia. Tutkimusdata on kerätty puolistrukturoiduista haastatteluista, joissa haastateltiin kymmentä terveydenhuollon ammattilaista Ruotsista, Saksasta ja Iso-Britanniasta. Pro gradu -tutkielman tulokset osoittavat, että terveydenhuollon ammattilaiset Ruotsissa, Saksassa ja Iso-Britanniassa arvostavat vastuullisuutta ja kuivajauheinhalaattorien ympäristöystävällisyydellä on positiivinen vaikutus valittaessa hoitomuotoa. Tärkeimpänä ominaisuutena hoitomuodon valinnassa kuitenkin korostui turvallisuus sekä potilaan kyvykkyys käyttää lääkevalmistetta oikein optimaalisimman hoitotuloksen aikaansaamiseksi. Mikäli potilas pystyi kuivajauheinhalaattoria adekvaatisti käyttämään, niin terveydenhuollon ammattilaiset suosivat ensisijaisesti ympäristöystävällisempiä kuivajauheinhalaattoreita ponnekaasuaerosolien sijaan. Tämän ansiosta kuivajauheinhalaattoreita tuottavat lääkevalmistajat voivat saada kilpailuetua verrattaessa vain ponnekaasuaerosolia tuottaviin lääkevalmistajiin. Tutkimuksen löydökset viittaavat myös siihen, että kuivajauheinhalaattoreita tuottavien lääkevalmistajien on hyödyllistä jakaa laajasti ympäri maailmaa tietoa terveydenhuollon ammattilaisille eri inhalaattorien ympäristövaikutuksista. Todennäköisintä kuitenkin on, että merkittävin ero ponnekaasuaerosolien ja kuivajauheinhalaattorien käytön välille saadaan vastuullisuuteen pyrkivien säädöksien ja lakien kautta.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business